2021
DOI: 10.1002/adfm.202102468
|View full text |Cite
|
Sign up to set email alerts
|

Morphology Control in 2D Carbon Nitrides: Impact of Particle Size on Optoelectronic Properties and Photocatalysis

Abstract: The carbon nitride poly(heptazine imide), PHI, has recently emerged as a powerful 2D carbon nitride photocatalyst with intriguing charge storing ability. Yet, insights into how morphology, particle size, and defects influence its photophysical properties are virtually absent. Here, ultrasonication is used to systematically tune the particle size as well as concentration of surface functional groups and study their impact. Enhanced photocatalytic activity correlates with an optimal amount of those defects that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 80 publications
1
59
0
Order By: Relevance
“…Hence, conductivity can be an additional important parameter in tuning photocatalysts besides other, often intertwined properties, affecting the efficiency of the process. [ 12 ]…”
Section: Resultsmentioning
confidence: 99%
“…Hence, conductivity can be an additional important parameter in tuning photocatalysts besides other, often intertwined properties, affecting the efficiency of the process. [ 12 ]…”
Section: Resultsmentioning
confidence: 99%
“…A further aspect to be considered in semiconductor photocatalysis is the catalyst particle size. Many studies have investigated particle size effects for different photocatalysts and found that the interplay of factors such as specific surface area [61,62], charge-carrier dynamics [63,64] and light absorption [63,65] is crucial. Especially, if photocatalysts of similar composition are compared, the explanation of observed differences in catalytic activity needs to consider particle size effects, which are hardly covered by existing FOMs [66].…”
Section: •Rmentioning
confidence: 99%
“…1–4 As a “rising star” in photocatalysis, g-C 3 N 4 has attracted great interest because of its moderate bandgap (2.7 eV), nontoxicity and wide material sources. 5–9 Generally, g-C 3 N 4 is obtained by thermal condensation of C/N-rich precursors (urea, cyanoguanidine, etc. ).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] As a "rising star" in photocatalysis, g-C 3 N 4 has attracted great interest because of its moderate bandgap (2.7 eV), nontoxicity and wide material sources. [5][6][7][8][9] Generally, g-C 3 N 4 is obtained by thermal condensation of C/N-rich precursors (urea, cyanoguanidine, etc.). Due to the incomplete thermal polymerization, the product obtained is bulk g-C 3 N 4 with a specific surface area of less than 10 m 2 g −1 and limited solar-light absorption, resulting in its intermediate photocatalytic performance.…”
Section: Introductionmentioning
confidence: 99%